Quality housing: regulatory and administrative framework in Malaysia - Sufian, Azlinor; Ab Rahman, Rozanah (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
The housing industry in Malaysia is regarded as one of the major industries contributing to the economic and social development of the country. The industry is regulated by several sets of rules and the imposition of regulations, guidelines and standards is to ensure that all categories of houses, inclusive of houses for the lower income group will be constructed according to the acceptable standard. Despite the existence of these regulatory measures, yet there are many problems faced by house-buyers in Malaysia. This has to be affiliated with the level of commitment of housing developers as well as the enforcement of the above rules and regulations by the respective authorities. One of the most common problems encountered by the Malaysian house buyers is the sub-standard construction of houses. There is a standard form of sale and purchase agreement (SPA) stipulated under the Housing Development (Control and Licensing) Regulations 1989 (HD Regulations 1989) but as far as the problem of sub-standard construction of houses is concerned, Malaysian house-buyers are not well protected. In general there is no benchmark in Malaysia to measure the standard of quality of houses constructed by developers. It is the aim of this article to look into some recent amendments to the legal provisions (and its loopholes) concerning the statutory duties imposed on the three most important institutions related to the building of quality houses, namely the local authorities, the Ministry of Housing and Local Government (MHLG) and the Construction Industry Development Board (CIDB), in ensuring that houses constructed by developers will meet the quality that house-buyers expect. It is hoped that all quarters involved in the Malaysian construction industry be they professionals or semi professionals as well as policy makers will take into account the enforcement of the laws and practices in other jurisdictions as reference for the construction of quality houses.